2009
DOI: 10.4028/www.scientific.net/amr.62-64.203
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrated Cassava Chips Utilization in Starch and "Garri" Production

Abstract: Fresh cassava roots were processed to chips by peeling, washing,chipping, dehydration, and packaging. The dehydrated chips were thereafter processed to starch and garri by rehydrating the chips to 50-60% moisture. The products were compared with the ones produced from fresh cassava roots by evaluating the organoleptic properties, chemical compositions, and pasting characteristics. The garri from the dehydrated chips was ranked better in terms of particle size and aroma; while garri from fresh roots was ranked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(19 reference statements)
3
2
0
Order By: Relevance
“…The moisture content for gari samples were within the values considered acceptable for dried foods and also within the values reported for gari and other dried samples by earlier workers [12,13,21,22]. Ikujenlola et al [23] reported a value of 11.24% for gari processed from dehydrated cassava chips. Ash content, which is a measure of the mineral elements, was lowest in the control sample (1.33%) and highest in gari samples produced from chips dried at 70°C (1.70%).…”
Section: Proximate Composition and Cyanide Content Of Garisupporting
confidence: 85%
“…The moisture content for gari samples were within the values considered acceptable for dried foods and also within the values reported for gari and other dried samples by earlier workers [12,13,21,22]. Ikujenlola et al [23] reported a value of 11.24% for gari processed from dehydrated cassava chips. Ash content, which is a measure of the mineral elements, was lowest in the control sample (1.33%) and highest in gari samples produced from chips dried at 70°C (1.70%).…”
Section: Proximate Composition and Cyanide Content Of Garisupporting
confidence: 85%
“…The moisture content for cassava chips in the study were within the acceptable limits for dried foods and also closely conformed with values reported for chips and other dried samples by earlier studies [22,23]. Ikujenlolaand Omosuli [24] reported a value 11.24% forgari processed from dehydrated cassava chips. Ash content, which is a measure of the mineral elements was lowest in the local variety (2.08%) and highest in chips produced from the sweet variety (2.55%).…”
Section: Proximate Composition and Ph Of Chips From Selected Cassava ...supporting
confidence: 90%
“…The foaming capacity reduced from 5.22% in mature unripe seed to 4.98% in ripe seed and later increased to 6.13% in overripe seed. The foaming capacities of the samples with the range of 4.98-6.13% was found to be comparable to 6% reported for Sorghum bicolor L. stem flour [32] but higher than 4.00% recorded by [30] for common maize. Low foaming capacity (LGC) has been attributed to inadequate electrostatic repulsions, lesser solubility and hence excessive protein-protein interactions.…”
Section: Discussionsupporting
confidence: 64%
“…Bulk density (BD) content of mature unripe seed was found to be 0.98% which initially increased to 1.02% in ripe seed and later reduced to nearly the same value as the mature unripe seed; this may be due to microbial activities during ripening. The bulk densities of the three samples are higher than 0.77% reported for common maize sample [30]. Bulk density is greatly affected by particle size, solvents used for extracting the protein product [23] and method of drying [31].…”
Section: Discussionmentioning
confidence: 66%